2014
DOI: 10.19183/how.21.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Using Personal Portable Devices as Learning Tools in the English Class

Abstract: A group of university students used a variety of personal portable devices (cellphones, tablets, laptops, and netbooks) which distracted them in English class. This qualitative action research aimed to implement activities entailing the use of such devices and to learn their impact on students' learning and the use of English in class. Thus, a series of applications was used to promote the use of these devices for the benefit of the English as a Foreign Language class. These applications included a learning ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…With the rapid growth of mobile technologies as well as the explosion in the number of educational applications and mobile devices, a large number of studies have been conducted about the use of mobile devices in education [1][2][3][4]. Widespread ownership of mobile devices has cued researchers to pay attention to mobile devices as potential media to deliver learning content [5][6][7], and to consider how to use mobile devices as pedagogical support tools [8,9]. Educators have not only begun to use mobile technologies in formal classroom settings but have also integrated such technologies into informal education settings in daily life [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid growth of mobile technologies as well as the explosion in the number of educational applications and mobile devices, a large number of studies have been conducted about the use of mobile devices in education [1][2][3][4]. Widespread ownership of mobile devices has cued researchers to pay attention to mobile devices as potential media to deliver learning content [5][6][7], and to consider how to use mobile devices as pedagogical support tools [8,9]. Educators have not only begun to use mobile technologies in formal classroom settings but have also integrated such technologies into informal education settings in daily life [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…A third group of studies is made up of exploring how student-teachers use technology innovations. In the research conducted by Herrera, Cruz, and Sandoval (2014) in a university in Mexico, student-teachers implemented the use of portable devices in order to improve students' performance in the English class and found that it is a significant and efficient tool for learning because students feel enthusiastic to participate. In the research carried out by Espitia and Kwinta (2012), they implemented the Buddy System, a system that helps to promote online interaction among students of the English courses in Universidad de la Sabana in Colombia.…”
Section: Other Paths Other Walkersmentioning
confidence: 99%
“…These technological devices (e.g., laptops, tablets, smartphones, etc.) have allowed students to collect and synthesize information easily and classroom settings as technology has developed and its use increased in recent years (Herrera Díaz, Cruz Ramos, & Sandoval Sánchez, 2014;Ifenthaler & Schweinbenz, 2013;Kim et al, 2014;Moran, Hawkes, & El Gayar, 2010).…”
Section: Introductionmentioning
confidence: 99%